THE LANGUAGE OF PHILOSOPHY OF ABU NASR AL-FARABI: FEATURES OF THE TRANSLATION OF MEDIEVAL TEXTS - Sattarov Muhitdin Ortiqovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the author, using scientific and historical sources, tried to substantiate the subject of research taking into account scientific objectivity. In the course of his research, he briefly showed the life, activities and process of al-Farabi's education and travels, in this regard, referring to the ancient and medieval schools of the East, clearly showed al-Farabi's place in the culture of the "House of Wisdom" on the basis of scientific sources.